General steady-state solution and Green”™s functions in orthotropic piezothermoelastic diffusion medium (Archives of Mechanics - Test, 2013)
The present investigation deals with the study of Green’s functions in orthotropic piezothermoelastic diffusion media. With this objective, firstly the two-dimensional general solution in orthotropic piezothermoelastic diffusion media is derived. On the basis of general solution, the Green function for a point heat source and chemical potential source in the interior of semi-infinite orthotropic piezothermoelastic diffusion material is constructed by five newly introduced harmonic functions. The components of displacement, stress, electric displacement, electric potential, temperature change and chemical potential are expressed in terms of elementary functions. Since all the components are expressed in terms of elementary functions, this fact makes them convenient to use. From the present investigation, a special case of interest is also analyzed to depict the effect of diffusion. Resulting quantities are computed numerically and presented graphically to illustrate the effect of diffusion.